M=(9x+7)

Simple and best practice solution for M=(9x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for M=(9x+7) equation:



=(9M+7)
We move all terms to the left:
-((9M+7))=0
We calculate terms in parentheses: -((9M+7)), so:
(9M+7)
We get rid of parentheses
9M+7
Back to the equation:
-(9M+7)
We get rid of parentheses
-9M-7=0
We move all terms containing M to the left, all other terms to the right
-9M=7
M=7/-9
M=-7/9

See similar equations:

| 1/8(x-2)=1/3(3x+1) | | x4+11=19 | | 5(3e+1)=35 | | (2x+3)²=10-(x²+2x-8) | | (-2x+1)-(2x-8)=13 | | 7x-42=3x+18/ | | 10+1+7f=10f−7 | | 3a+(2a+6);a=2 | | 25x–450=–325 | | 5p-11=3 | | –10+10t=9t−3 | | 0.65xx=5.20 | | x=0.65x8 | | 0.65x8=x | | 2(x+1)+4=3(x+2) | | x3-7=-20 | | F=17x-1 | | 16=(2+n) | | 6n-2n=5-7 | | 5x^2−16x+13=10 | | 10+6(8x-5)=28 | | 2(3x+6)=3x-6 | | 20+17u=-6+5u | | 5(x+3)+7x=3(x-10) | | 3t=5.7 | | 17=(14+19+q)/3 | | 21=5x+3x-2x | | Y+12+2y=69 | | 2e​−6=8 | | 13x−56=23 | | 5x−1)/2−x/3=142/15 | | x7−3=57 |

Equations solver categories